2022
DOI: 10.3390/ma15238681
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Polyphosphates Acid and Different Compounds of Waste Cooking Oil on Conventional and Rheological Properties of Modified Bitumen

Abstract: In order to conserve non-renewable natural resources, waste cooking oil (WCO) in bitumen can help lower CO2 emissions and advance the environmental economy. In this study, three different components of WCO were isolated and then, together with polyphosphoric acid (PPA), used separately as bitumen modifiers to determine the suitability of various substances in WCO with PPA. Conventional tests, including penetration, softening point temperature, and ductility, and the dynamic shear rheology (DSR) test, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…The significant improvement in the I-value of the virgin bitumen after incorporating the three molecular-weight WCO components can be attributed to the fact that each of the different molecular-weight WCOs contains a certain number of lighter components that complement the resins, aromatics, and saturates of the virgin bitumen. Moreover, the solubilization of asphaltenes by the light fraction also promotes the recovery of the colloidal structure [37,38]. In contrast, the I-value gradually decreases with the increase in PPA content.…”
Section: 𝐼 = 𝑅 + 𝐴 𝐴 + 𝑆mentioning
confidence: 99%
See 1 more Smart Citation
“…The significant improvement in the I-value of the virgin bitumen after incorporating the three molecular-weight WCO components can be attributed to the fact that each of the different molecular-weight WCOs contains a certain number of lighter components that complement the resins, aromatics, and saturates of the virgin bitumen. Moreover, the solubilization of asphaltenes by the light fraction also promotes the recovery of the colloidal structure [37,38]. In contrast, the I-value gradually decreases with the increase in PPA content.…”
Section: 𝐼 = 𝑅 + 𝐴 𝐴 + 𝑆mentioning
confidence: 99%
“…The SARA fraction content is a crucial factor affecting the stability of the bitumen colloid system and the bitumen properties [36,37]. The results of the SARA content of WPmodified bitumen are shown in Figure 8.…”
Section: Saramentioning
confidence: 99%
“…It was found that the feasibility of improving the low-temperature crack resistance of asphalt and its mixture by PPA alone was low, and it needed to work together with other polymers or rubber modifiers. Therefore, in recent years, researchers have gradually turned to the study of multiphase composite modified asphalt [26][27][28][29]. For example, Yajin Han et al [30] found that an appropriate amount of PPA can reduce the phase separation phenomenon of SBR modified asphalt, and its low-temperature performance degradation is not significant.…”
Section: Introductionmentioning
confidence: 99%
“…This technology not only contributes to sustainable practices, but also offers economic advantages by lowering production costs [12,13]. Another promising technology is the introduction of recycling agents or modifiers specifically designed for RAP [14]. These additives, such as polymers, chemical agents, and bio-rejuvenators, aim to restore the aged binder in RAP materials and improve their rheological properties [15].…”
Section: Introductionmentioning
confidence: 99%